Influence of environmental variables on the predatory sucess of the iberian wolf in the north of Portugal - Silva, Inês Bernardino da (2016)
Tese de mestrado em Biologia da Conservação, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2016